Particles dissolution and liquid mixing dynamics by Electrical Resistance Tomography. (February 2020) - Paglianti, Alessandro; Maluta, Francesco; Montante, Giuseppina
Salt particles dissolution in slurry stirred tanks provides an ambitious challenge for the application of Electrical Resistance Tomography in the process industry, because the presence of high loadings of inert particles requires a purposely developed post-processing method of the experimental data. For the optimization of the working conditions of the dissolution process, two characteristic times are required: the time for the liquid homogenization in the tank and the time required for the complete dissolution of the salt particles. The former time has been experimentally determined in previous investigations both in stirred tanks working with single-phase and with multiphase mixtures. The latter characteristic time has not been analyzed so far, due to the lack of experimental procedures for distinguishing it from the former. In this work, a novel approach for the simultaneous identification of the two characteristic times is presented. The impact of the new procedure is significant for the production processes, since it offers a tool for identifying when the soluble particle size has an impact on the dissolution dynamics, and when the stirred tank dynamics is influenced by the liquid homogenization only, and therefore a reduction of the particle size does not speed up the process accomplishment.